Escala de percepção da corrupção: construção e validação - Cunha, Ricardo Teixeira (2021)
The theme of corruption is intriguing and worthy of in-depth studies in view of its most diverse facets, in a theoretical and empirical way, aiming to carry out new analyzes and expand the existing knowledge. Rose-Ackerman's seminal studies leverage the theme, which has been expanded since the 1980s in order to study the relationship between corruption and economic and social effects, for example. Given the complexity of the phenomenon itself, measuring its perception represents a similar difficulty, being rare and whose advances are of great relevance. Thus, the present work aimed to build and validate the Corruption Perception Scale (EPC) from the perspective of the Brazilian citizen. To achieve the proposed objective, 1,075 questionnaires were applied throughout the Brazilian national territory, through the virtual environment. The instrument was submitted to Expert Analysis who verified the pertinence and relevance of the items, as well as their semantic analysis and understanding of the instructions provided. Most respondents considered the political class to be totally corrupt (43.1%) and the country Brazil to be very corrupt (49.1%), which is reiterated by the fact that 76.3% of respondents consider that there is a total impact of corruption on the politics and 73.6% believe that public investments are equally fully impacted by corruption. Through multivariate analysis, six dimensions were validated and came to constitute the Corruption Perception Index: Knowledge, Contact, Reflections, Confrontation, Consequences and Tolerance. The Corruption Perception was classified as “Very Low”, “Low”, “High” and “Very High”, enabling the applicability of the Corruption Perception Scale (EPC). Once applied the EPC in Brazilian citizens, Brazil's Corruption Perception was classified as “High”. Among several benefits, EPC can be interesting for the analysis of differences in perception among different socioeconomic profiles and different countries, considering that it brings an analysis from the point of view of citizen. Finally, future studies may seek to incorporate new dimensions, validation in other samples or adaptation to different cultures.